Surgery for metastatic spinal differentiated thyroid cancer: feasibility, outcome, and prognostic factors - Liu, Xiajun; Hu, Panpan; Zhai, Shuheng; Liu, Xiao; Wang, Ben; Zhou, Hua; Liu, Xiaoguang; Liu, Zhongjun; Wei, Feng (Frontiers in Surgery, 2023)
Study design A retrospective cohort study. Objectives This study aims to report the surgical outcome of metastatic spinal differentiated thyroid cancer (MSDTC) and analyze the factors affecting the prognosis. Methods Thirty-five patients were recruited in our single institution who underwent spinal surgery and adjuvant therapies from 2009 to 2019. Two surgical procedures, total en-bloc spondylectomy and debulking surgery, were undertaken. Their clinical data, postoperative events, and survival data were collected and analyzed. Survival time and associated factors were further analyzed. Results The cohort had a median survival time of 60 months. The mean visual analog scale scores and the Karnofsky performance score improved postoperatively (p < 0.05). The patients' Frankel grade was elevated for cases with preoperative neurological deficits (p < 0.05). In 31 patients who underwent debulking surgery, 41.9% (n = 13) had local recurrences, and radiotherapy reduced the risk of local relapse (p < 0.05). Preoperative and postoperative Frankel grades and radioactive iodine (RAI) therapy were associated with the patients’ survival in the univariate analysis (p < 0.05). Furthermore, a multivariate regression analysis showed the postoperative Frankel grade as an independent prognostic factor. Conclusion Pain, quality of life, and neurological status of patients can be effectively improved after surgery. Radiotherapy can reduce the risk of local recurrences, whereas RAI therapy has a limited effect on local and extraspinal tumor control. Neurological status was independently associated with the patients' survival.